2020
DOI: 10.1108/apjml-06-2019-0397
|View full text |Cite
|
Sign up to set email alerts
|

How do followers infer the motives behind an influencer's advertising disclosures?

Abstract: PurposeIn the context of influencer marketing, this study examines the effects of explicit advertising disclosure on consumers' inference regarding influencers' sincere recommendation intent, and its consequences for consumers' purchase intentions.Design/methodology/approachIn Study 1, participants were randomly assigned to the conditions of explicit advertising disclosure (e.g. #AD, #Sponsored) and subtle advertising disclosure (e.g. #ThankYou), and indicated their inference regarding influencers' recommendat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 43 publications
(60 reference statements)
0
9
0
4
Order By: Relevance
“…When disclosure cues are present, they can reveal the nature of the SMI–brand partnership explicitly (i.e. specifying the type of compensation) or implicitly (by remaining evasive about the type of retribution) (Boerman and van Reijmersdal, 2016; Carr and Hayes, 2014; Wojdynski et al, 2018), use very clear language (“partnership paid for by”) or more nebulous industry jargon (@brand, #brand or #ad #sp advertising) (Evans et al, 2017; Han et al, 2020). Such decisions are very complex for SMIs (Wellman et al, 2020).…”
Section: Disclosure Of Sponsored Content: a Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…When disclosure cues are present, they can reveal the nature of the SMI–brand partnership explicitly (i.e. specifying the type of compensation) or implicitly (by remaining evasive about the type of retribution) (Boerman and van Reijmersdal, 2016; Carr and Hayes, 2014; Wojdynski et al, 2018), use very clear language (“partnership paid for by”) or more nebulous industry jargon (@brand, #brand or #ad #sp advertising) (Evans et al, 2017; Han et al, 2020). Such decisions are very complex for SMIs (Wellman et al, 2020).…”
Section: Disclosure Of Sponsored Content: a Literature Reviewmentioning
confidence: 99%
“…A third group of studies examines the effects of disclosing advertising on evaluating sources. They reveal that ad disclosure damages perceptions of the source in terms of attitudes (van Reijmersdal et al, 2020), perceptions of source’s honesty (Han et al, 2020), perceptions of trust (De Jans et al, 2018; Dhanesh and Duthler, 2019), and perceptions of source’s credibility (Colliander and Erlandsson, 2015). However, some studies find no impact (Dhanesh and Duthler, 2019), especially if the disclosure statement is very explicit (Carr and Hayes, 2014) or if the SMI adds a fairness statement, such as “honest opinions” (Hwang and Jeong, 2016), or if the message is balanced, including positive and negative arguments (message laterality) (De Veirman and Hudders, 2019).…”
Section: Disclosure Of Sponsored Content: a Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…From the record of each collaboration, we identified whether or not it was accompanied by a disclosure before noting whether this disclosure was explicit or ambiguous based on three conditions: (a) language used for the disclosure, (b) visibility (visible size and location), and (c) type of text (hashtag, phrase, abbreviations). When the disclosure met all three conditions (e.g., "Paid partnership with" or "#Advertising"), it was scored as explicit, and when it was written in English or abbreviated, contained euphemisms, and/or was not visible at first glance (e.g., "#Ad," "#Thanks," "Gifted," "#Sponsored," or "Sp"; Han et al, 2020), it was scored as subtle/ambiguous. When no disclosure was detected, it was scored as zero.…”
Section: Measurementsmentioning
confidence: 99%
“…This may be due to conflicting extant research investigating consumer responses to branded posts. For instance, research suggests the presence of a disclosure can affect how consumers process and recognize advertisements (Evans, Phua, Lim, and Jun 2017), as well as their attitudes toward a brand (Boerman, Willemsen, and Van Der Aa 2017;Campbell, Mohr, and Verlegh 2013), online sharing intention (Evans et al 2017) and purchase intention (Han, Yi, Jun, and Ahn 2020). In particular, Boerman and colleagues (2017, 82) found that sponsorship disclosure can reduce the persuasive effect of the sponsored post, and if the message includes a celebrity endorser, consumers often develop "distrusting beliefs about the post" which "decreases their intention to engage in electronic word of mouth" behaviors such as liking or commenting on the post.…”
Section: Athlete Disclosure Of Brand Relationshipsmentioning
confidence: 99%